Représentations de l’insécurité et usages de la violence armée - Taline Papazian (Études Arméniennes Contemporaines, 2014)
This article examines the genesis of political sovereignty among Jews and Armenians in the Ottoman and Russian empires from the end of the 19th century onwards and throughout the 20th century. It questions the interaction between representations of physical security and uses of armed violence within the trajectories of political sovereignty, which will be tracked down focusing on four experiences of use of armed violence by these communities. These experiences took place in different times and places; they were handled sometimes by institutional actors, sometimes not. This diversity allows questioning the presence or absence of a notion of sovereignty – possibly with a plurality of meaning – coming to light through the use of armed violence.